Pengaruh AI Marketing dan Live Shopping Experience terhadap Loyalitas Pelanggan Generasi Z di Kec. Karangsembung, Cirebon : Studi Kasus Pada Tiktok Shop - Ade Rahmawati; Dumadi Dumadi; Azizah Indiyani; Slamet Bambang Riono (CV. ALIM'SPUBLISHING, 2026)
The rapid development of digital technology has encouraged the adoption of AI Marketing and Live Shopping Experience as marketing strategies to enhance customer loyalty on e-commerce platforms, particularly TikTok Shop. However, studies examining the influence of these two variables on Generation Z customer loyalty in non-metropolitan areas remain limited. This study aims to analyze the effects of AI Marketing and Live Shopping Experience on the customer loyalty of Generation Z in Karangsembung District, Cirebon. A quantitative research approach was employed using a survey method involving 350 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through multiple linear regression with SPSS. The findings indicate that AI Marketing has a positive and significant effect on customer loyalty. Likewise, Live Shopping Experience also has a positive and significant effect on customer loyalty. Simultaneously, AI Marketing and Live Shopping Experience significantly influence customer loyalty, with a coefficient of determination of 35.4%, while the remaining 64.6% is explained by other factors outside the research model. These findings suggest that AI-based personalization and interactive live shopping experiences enhance customer trust, satisfaction, and repurchase intentions, thereby strengthening customer loyalty. This study provides practical implications for businesses to optimize AI Marketing and improve the quality of Live Shopping as effective strategies for increasing Generation Z customer loyalty on TikTok Shop.